How can modelling tools inform environmental and conservation policies? - Mohd, Mohd Hafiz (International Journal of Engineering and Technology, 2018)
Among the important environmental and ecological problems are to determine the distributions of species (e.g. endangered, native and invasive species) across geographical regions and to understand the determinant of species range limits (i.e. the boundaries of the locations in which a species is found). Various studies highlight that abiotic environments (e.g. temperature, climate) and biotic interactions (e.g. competition) can influence species distributions. To investigate this problem, two mathematical models for predicting species distributions have been employed. Such models generally take the form of deterministic systems such as partial-differential equations, in which they aim to understand the interactions between species at the population scale. Thinking of interacting species as finite groups of agents, rather than continuous densities, may alter the structure of the modelling frameworks. This problem can be studied using stochastic individual-based models (IBM). These two models are used to examine the outcomes of species interactions and to understand how these species are distributed in spatially changing environments. As such, comparing and contrasting the observations between the IBM and deterministic models may offer important insights in predicting species range limits and help us to develop robust predictions of species potential distributions in nature.